KERJASAMA KEPOLISIAN NEGARA REPUBLIK INDONESIA DAN KEPOLISIAN FEDERAL AUSTRALIA MENANGGULANGI CYBERCRIME DI INDONESIA - Noviyanti, Indri; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Cybercrime as particularly vulnerable to transnational crime in Indonesia, itsbecause there were no enforcementâ€™s. Indonesia there was no specific legislationwhich owned by the Indonesian cybercrime and limited facilities and infrastructurerelatedagencies in the field of technology. Negative impacts caused by cybercrimenot only harm the individual, society and state but also can threaten a country both interms of security, economic, social and cultural. â€œHowever, the relationship betweenIndonesia and Australia disrupted after wiretapping of Australia, Indonesia feltaggrieved by it that Indonesia protested in Australia, and these conditions clearlyhave reduced the trust Indonesia to Australia.â€This study applies neorealist perspective, theory assumes that internationalcooperation to develop themselves, any country cooperating with other countriesinternationally accepted and cooperation can not be avoided because each countryhas a national interest. This study applies qualitative research method with libraryresearch.The result of this research shown wiretapping that has been done Australia noimpact on cooperation between Polri and the Australian Federal Police (AFP)tackling cybercrime in Indonesian, proved by doing SOM between Polri and the AFPon 3th-6th November 2013 and training programs at JCLEC between Polri and AFPon 7th April 2014. Polri still continue cooperation with the AFP after wiretapping ismotivated by some of the help given Australia toward Indonesia, that is assistance inlaw enforcement, human resources, equipment and technologies that provide apositive impact for Polri tackling cybercrime in Indonesia.Keywords: Australian Federal Police, cooperation, cybercrime, Polri, transnationalcrime